2022
DOI: 10.1002/pc.26533
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, thermogravimetric, and dynamic mechanical analysis of basalt and flax fibers intertwined vinyl ester polymer composites

Abstract: The selection of fibers and their stacking sequence, which affect structural integrity and functional properties, are critical parts of polymer composite design. In this work, the influence of various stacking sequences made of basalt and flax fiber layers on the mechanical, thermal, and dynamic mechanical analyses of vinyl ester polymer composites was investigated. The stacking sequence designed by alternate basalt and flax layers showed higher tensile and flexural strengths, with basalt layers in the outer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…Figure 8A–F shows the typical tensile fractured surface of FMLs. It is seen that fiber breakage/pull‐out, fiber‐matrix debonding, void, and delamination were observed 38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 8A–F shows the typical tensile fractured surface of FMLs. It is seen that fiber breakage/pull‐out, fiber‐matrix debonding, void, and delamination were observed 38 …”
Section: Resultsmentioning
confidence: 99%
“…It is seen that fiber breakage/pull-out, fiber-matrix debonding, void, and delamination were observed. 38 Delamination-based failure due to the de-adhesion between the metal sheet-matrix was observed in FMLs. 13 Besides, some of the split fibers are seen in the SEM images.…”
Section: Typical Fracture Surface Analysismentioning
confidence: 99%
“…The motion of EPU chains might be restricted after the addition of BF according to these results. [ 64–68 ]…”
Section: Resultsmentioning
confidence: 99%
“…The motion of EPU chains might be restricted after the addition of BF according to these results. [64][65][66][67][68] Tan δ curves in Figure 6 revealed that BF inclusions led to an increase in Tan δ of unfilled EPU. Similar to storage modulus findings, extensions in Tan δ of EPU were found to be higher amounts for composites filled with ES-BF and ER-BF.…”
Section: Dynamic Mechanical Characterizationmentioning
confidence: 99%
“…It can be concluded that the existence of the fewer amount of voids, good adhesion behavior among fabrics and matrices, proper fiber breakage, and pull-out characteristics of the laminates makes them suitable for certain medium load engineering applications. [67][68][69][70][71][72]…”
Section: Sem Analysismentioning
confidence: 99%